Acute epileptiform abnormalities are the primary predictors of post‐stroke epilepsy: a matched, case–control study. Issue 4 (3rd March 2022) - Punia, Vineet; Ellison, Lisa; Bena, Jim; Chandan, Pradeep; Sivaraju, Adithya; George, Pravin; Newey, Christopher R.; Hantus, Stephen
Abstract: Stroke patients who underwent continuous EEG (cEEG) monitoring within 7 days of presentation and developed post‐stroke epilepsy (PSE; cases, n = 36) were matched (1:2 ratio) by age and follow‐up duration with ones who did not (controls, n = 72). Variables significant on univariable analysis [hypertension, smoking, hemorrhagic conversion, pre‐cEEG convulsive seizures, and epileptiform abnormalities (EAs)] were included in the multivariable logistic model and only the presence of EAs on EEG remained significant PSE predictor [OR = 11.9 (1.75–491.6)]. With acute EAs independently predicting PSE development, accounting for their presence may help to tailor post‐acute symptomatic seizure management and aid anti‐epileptogenesis therapy trials.